Tourism sector and environmental quality: Evidence from top 20 tourist destinations - Ozcan, Burcu; Bozoklu, Seref; Khan, Danish (Springer, 2020)
This chapter aims to analyze the effect of the tourism sector on environmental quality for France, Spain, the United States, China, Italy, Turkey, Mexico, Germany, Thailand, the United Kingdom, Japan, Austria, Greece, Honk-Kong, Malaysia, Russian Federation, Portugal, Canada, Poland and the Netherlands for 1995-2018. The empirical results indicate that the development of the tourism sector reduces both CO2 emission and ecological footprint and the environmental Kuznets curve hypothesis is confirmed for CO2 emission but not for ecological footprint. The findings also reveal that energy consumption degrades the environment in both forms of air pollution and social pressure, and financial development alleviates CO2 emission; however, it does not affect ecological footprint. All these results suggest that the tourism sector should be supported by the collaboration of the private sector and government. © The Author(s) 2021. All rights reserved.